Addressing the pilot shortage: funding flight training at Asheville-Buncombe Technical Community College - Corman, Richard Justin (2023)
The United States (US) airline industry is currently experiencing a pilot shortage that could quadruple between the years 2022 - 2025 (Baldwin, 2022). Although there is not a single cause for this pilot shortage, one of the reasons is the high cost of entry into the industry (Silk, 2019). For aspiring pilots to enter the aviation and/or airline industry as a professional pilot you must obtain at least a commercial pilot license with an instrument rating and multi-engine privileges. The cost to earn these credentials can total at least $40,000 (WNC Aviation, 2018). Given that many community and technical colleges across the country do not own aircraft to perform flight training, the cost of flight training falls onto the students in flight training. To assist students with obtaining the necessary funding for flight training, the use of a College Foundation of North Carolina (CFNC) Student Assist Loan was implemented as an improvement initiative.